Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, Risiko, Keamanan, dan Kepercayaan terhadap Penggunaan Digital Banking - Ketty Junisa Piandari Utami; Vika Fitranita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, perceived risk, security, and trust on the use of digital banking services. This study used a quantitative approach with a survey method. Data were collected by distributing questionnaires to 170 digital banking users in Bengkulu City, selected using a purposive sampling technique. Data analysis was performed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results show that perceived usefulness, perceived ease of use, security, and trust have a positive and significant influence on the use of digital banking services. This suggests that perceived usefulness, ease of use of the system, level of service security, and trust in the service provider are important factors that encourage users to utilize digital banking services. Conversely, perceived risk did not significantly influence the use of these services. This study contributes to the development of the Extended Technology Acceptance Model (Extended TAM) by incorporating variables such as perceived risk, security, and trust to explain technology usage behavior in the digital banking sector. In addition, this research also provides practical implications for the banking industry in improving the quality of digital banking services, especially in terms of ease of use, system security, and building user trust.